(untitled) (مجلة ديالى للبحوث الانسانية, 2025)
The purpose of this study is to provide insight into old myths and mythologies by focusing on the poetic image of "Rebirth" from various points of view by analyzing the interpretations and references to which two distinct cultures, Arab and American, in contemporary poetry. This image will be investigated by examining the poetry writings of many poets from both cultures. Poems written by poets will be selected depending on the legendary figures of Tammuz, Adonis, Christ’s Rebirth, Icarus, the Phoenix, and mythical creatures to express their viewpoints and demonstrate their creative worth in order to warn people to transform their present reality into a better one. Poets from the Arab world, such as Adunis and Yousuf El-Khal, and poets from America, such as Edward Fields and Leslie Marmon Silko attempted to connect Arabs and Americans in the present situation to the reader by conveying a metaphysical search to portray their suffering and optimism and to find an exile to enhance the dominant situations.